Faktor-Faktor Yang Berpengaruh Terhadap Nilai Perusahaan Pada Perusahaan Property dan Real Estate Yang Terdaftar Di BEI Periode 2020-2024 - Selina Dila Profita; Maryono Maryono; Batara Daniel Bagana (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The primary objective of this study is to analyze how financial variables specificall, investment decisions, dividend policy, and firm size shape firm value within the real estate and property industry on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. Employing a quantitative approach, this research processed annual data from 80 selected samples. The results of the hypothesis testing reveal several compelling findings: influence firm value. Conversely, dividend policy proved to be a powerful positive driver demonstrated a significant negative effect. Collectively, these variables influence firm value simultaneously, leading to the conclusion that dividend mechanisms serve as the most crucial instrument for investor valuation within the property sector.